Case Report: High Doses of Intravenous Immunoglobulins as a Successful Treatment for Late Onset Immune Agranulocytosis After Rituximab Plus Bendamustine - Diez-Feijóo, Ramon; Rodríguez-Sevilla, Juan Jose; Fernández-Rodríguez, Concepcion; Flores, Solange; Raya, Carmen; Ferrer, Ana; Colomo, Luis; Salar, Antonio (Frontiers in Immunology, 2022)
Late onset neutropenia (LON) related to rituximab or rituximab plus chemotherapy is defined as an unexplained absolute neutrophil count of ≤1.5 × 109/L starting at least four weeks after the last rituximab administration. LON is infrequent and its pathophysiology remains unknown. There are no guidelines or consensus strategies for the optimal management of patients developing LON. The majority of the patients recover promptly with no specific treatment and only some cases need to be managed with granulocytic colony stimulating factor (G-CSF), usually with a rapid response. Here, we describe a 69-year-old patient with Waldenström’s macroglobulinemia who presented a septic event in the context of severe LON after rituximab plus bendamustine. The diagnosed of agranulocytosis was established by bone marrow examination. Interestingly, anti-neutrophil antibodies bound to the patient’s granulocytes were found suggesting an autoimmune mechanism. The patient did not respond to G-CSF but achieved a rapid response after high doses of intravenous immunoglobulins with full white blood cell recovery.